A Contrastive Analysis of Modality Markers in US Presidential Election Debates by Hillary Clinton and Donald Trump - Nguyen Thi Kieu Phuoc
Chapter one. Introduction; Chapter two. Literature and theoretical; Chapter three. Research design and methodology; ...